TINGKAT PENGETAHUAN IBU HAMIL TENTANG HYPNOBIRTHING - Bringiwatty Batbual; Namsyah Baso; Yurissetiowati, Yurissetiowati; Melinda Rosita Wariyaka; Tri Maryati; Fransiskus Salesius Onggang (Bajang Institute, 2025)
Hypnobirthing is a painless birthing technique without the involvement of medicine through relaxation techniques using self-hypnosis and a natural birth process. The aim of this community service activity is to increase pregnant women's knowledge about hypnobirthing. The method of this community service activity is by providing counseling or outreach about hypnobirthing and hypnobirthing demonstrations for pregnant women. Participants in this activity were 15 pregnant women aged 30 - 35 weeks' gestation in the East Penfui Pustu area. This community service activity is carried out by distributing pretest questionnaires, then providing materials and demonstrations, then evaluation is measured using a posttest questionnaire. The result of this community service activity is an increase in pregnant women's knowledge about hypnobirthing. The conclusion from this community service activity is that providing hypnobirthing material to pregnant women is a good way to increase the knowledge of pregnant women and is considered quite successful. In the future, activities similar to this will be carried out with a larger number of participants so that the benefits can be felt by more pregnant women.